Exploring the spatiotemporal trends of extreme sub-hourly rainfall erosivity: Insights from karst plateaus in China - Youjin Yan; Xin Wang; Zeyin Hu; Xiaojin Xu; Quanhou Dai; Lina Mei; Fengling Gan; Huifang Jin; Liangjie Wang; Chenyang Huang (Journal of Hydrology: Regional Studies)
Study region: The karst plateau region in Southwest China. Study focus: Global warming has increased the frequency and intensity of extreme rainfall events, exacerbating soil erosion. Traditional assessment methods using daily, monthly, or annual data struggle to capture individual rainfall impacts, especially in regions with frequent extreme rainfall due to global warming. This study used high-resolution satellite data to analyze extreme sub-hourly rainfall erosivity in karst plateau areas. New hydrological insights for the region: The results indicate that sub-hourly rainfall scales accurately reflect the temporal dynamics of rainfall events. In the study area, 95 % of the events fell below the critical soil erosion threshold (30 mm·h−1), suggesting that traditional cumulative rainfall scales may overestimate erosivity compared to the impact of high-intensity, short-duration events captured at the sub-hourly level. High-erosivity regions have experienced decelerating increases, whereas low-erosivity regions have seen significant rises. After 2014, the annual maximum rainfall erosivity shifted from a significant decreasing trend to an increasing state accompanied by a shortening peak periodicity. Maximum annual rainfall erosivity occurs in spring (May), while the erosive rainfall events in winter are increasing in intensity. Consequently, low-erosivity regions and winter rainfall events pose a rising risk of soil erosion. This study provides a scientific basis for targeted erosion control measures, emphasizing the need for enhanced monitoring, early warning systems, and soil and water conservation to effectively address the challenges posed by rainfall erosion.